Knowledge and acceptance of male circumcision as an HIV prevention procedure among plantation workers at Border Limited, Zimbabwe - Mhangara, Taremeredzwa (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2011.